Abundance of selected bacterial groups in healthy calves and calves developing diarrhea during the first week of life: Are there differences before the manifestation of clinical symptoms? - Schwaiger, Karin; Storch, Julia; Bauer, Christoph; Bauer, Johann (Frontiers in Microbiology, 2022)
Background Diarrhea is still the most common and economically most significant disease of newborn calves. Objective Analysis of the development of selected bacterial groups in the feces of neonatal calves and its significance regarding diarrhea. Animals 150 newborn Simmental calves reared in 13 Bavarian farms were included in the study. Methods Fecal samples of calves taken at 0/6/12/24/48/72/168 hours (h) postpartum (pp) were analyzed qualitatively and quantitatively for aerobes, anaerobes, Enterobacteriaceae, E. coli, enterococci and lactobacilli using cultural, biochemical and molecular-biological methods. Concurrently, the health status of the animals was recorded. The bacterial levels of healthy and diarrheic animals were compared using statistical methods. In addition, feces samples from calves that developed diarrhea were examined by ELISA for the presence of rotaviruses, coronaviruses, E. coli F5 and Cryptosporidium (Cr.) parvum. Results Fifty-seven out of 150 calves (37.3 %) examined developed diarrhea within the first week of life. In the feces of calves with diarrhea on day 1 pp, the levels of aerobes, Enterobacteriaceae and E. coli were significantly increased, while significant differences (p<0.05) in enterococci and lactobacilli were not found. In animals with diarrhea onset on day 2, the lactobacilli were significantly reduced up to 24 h before the manifestation of clinical symptoms compared to healthy calves; for enterococci, this was only the case on the day of the onset of diarrhea. In addition, the ratios of aerobes, anaerobes, Enterobacteriaceae or E. coli to lactobacilli of calves with diarrhea on day 2 are significantly higher than those of healthy calves. The detection frequency of specific pathogens in diarrheic calves increased over the first week. Conclusion The results suggest that the incidence of neonatal diarrhea of calves is favored by low levels of lactobacilli in the feces. From this, the thesis can be derived that, in addition to an optimal supply of colostrum, the earliest possible administration of lactobacilli might reduce neonatal diarrhea in calves; however, this must be verified in a subsequent feeding experiment.